(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2023)
25 years after the first animal was cloned, the practice still remains restricted to a few devisions and countries. Despite all the potential implications, cloning remains contentious. In this article, we will look at the history of cloning, some of the arguments surrounding it, and its potential future applications.